Early mortality risk stratification in childhood bacterial meningitis using cerebrospinal fluid glucose and protein levels and their combinations: A multicontinental cohort study - Markku Kallio; Tuula Pelkonen; Irmeli Roine; Heikki Peltola (PLoS ONE, 2026)
Background Bacterial meningitis remains a major cause of death and neurological disability in children worldwide, particularly in low-resource settings where access to intensive care is limited. Cerebrospinal fluid (CSF) glucose, protein, and leukocyte concentrations are routinely measured at hospital presentation, yet their potential for early risk stratification – individually or in combination – has not been clearly defined. Because mortality risk is often difficult to assess at admission, identifying simple CSF-based thresholds that help clinicians recognize high-risk patients could improve triage and management globally. Methods and findings We evaluated CSF glucose, protein and leukocyte levels in 1598 children with bacteriologically confirmed bacterial meningitis across six countries in Latin America, Angola, and Finland to determine their individual and combined associations with mortality and neurological outcome. CSF glucose, protein, and leukocyte counts were measured at admission and examined in relation to in-hospital mortality and neurological outcome at discharge, as assessed by the Glasgow Outcome Scale. CSF glucose and protein concentrations were categorized into five clinically interpretable groups. Mortality increased progressively with decreasing CSF glucose (from 8% to 29%) and with increasing protein concentrations (from 5% to 23%). Children with both low CSF glucose (<10 mg/dL) and high CSF protein (≥200 mg/dL) had a mortality rate of 27% compared with 1% among those with normal CSF glucose and protein. A CSF leukocyte count <500/µL was also associated with increased mortality. Lower CSF glucose (ρ = 0.24; P < .001) and higher protein (ρ = 0.15; P < .001) were both associated with poorer neurological outcomes. Conclusions Routine CSF markers available at the time of hospital admission provide prognostic information that supports risk stratification in pediatric bacterial meningitis. Simple CSF-based thresholds—particularly when CSF glucose and protein are interpreted in combination—may help identify high-risk children early and guide clinical prioritization in settings with limited critical care capacity.